(untitled) (Jurnal Teknologi (Sciences & Engineering), 2025)
The application of carbon steel fiber metal laminate (CFML) has been increasing in engineering industries such as aerospace, automotive and processing industries. In fabricating CFML, the surface quality is a fundamental criterion as its stability is the key to avoiding delamination and corrosion. Delamination and corrosion can be prevented by growing a fresh and stable oxide layer with good mechanical properties via heat treatment on carbon steel. In this paper, the influence of heat treatment parameters namely temperature (400, 600 and 800 ⁰C), heating time (60, 90 and 120 min), heating rate (10, 15 and 20 ⁰C/min) and substrate roughness (P80, P240 and P800) on the X70 carbon steel oxide phase formation, thickness and hardness properties were investigated. Using Taguchi’s method, a total of 9 experiments were performed based on the L9 orthogonal array. The signal-to-noise ratio (S/N) and contribution percentage of the analysis of variance (ANOVA) of each parameter on the responses were studied. The optimal conditions for thickness were obtained at temperature 800 ⁰C, heating time 120mins, heating rate 10 ⁰C/min and sample prepared with P80 sandpaper grit. Meanwhile, optimal conditions for hardness were obtained at temperature 800 ⁰C, heating time 120mins, heating rate 10 ⁰C/min and sample prepared with P80 sandpaper grit.